UNITY EXISTS IN THE SUFISM DISCOURSE (COMPARATIVE STUDY OF IBN 'ARAB>I AND IBN SAB’>IN THOUGHT) (ENGLISH, ITALIC) - Ihwan Amalih; Fadilah (Media Inovasi Pendidikan dan Publikasi, 2023)
The study of man, God, and nature is part of the concept of unity of being that is an interesting object and never finished to be discussed. Various scientific disciplines talk about this, but what is still being discussed in the scientific discipline of Sufism. Sufism scholars have their own concept to discuss it. To find out more about the concept of unity of form, researchers use qualitative literature research. So this problem was raised again, because he wanted to know how the concept of unity of form according to two figures with a focus: 1. What is the meaning of unity of form according to Ibn 'Arab>i and Ibn Sab'>in. 2. How are the similarities and differences in the perspectives of Ibn 'Arab>i and Ibn Sab'>in. The methods used are descriptive, interpretive, and comparative methods. From this method, then the researcher processes and analyzes to obtain data. The primary data that the researcher took from the works written by these two figures. Based on the results of the research obtained is the concept of unity of form according to Ibn 'Arab>i, one form is God alone that exists, the being that he has created is simply to be his shadow. Meanwhile, according to Ibn Sab'>in, it is the form of God to be the principle of everything that exists both in the past, present, and future. All clear forms he returns to an absolute (spiritual) form. These two figures have similarities and differences in defining this concept. The equation in question, both of them place the form of God as the highest being and the other is only a shadow of Him. And the difference is, Ibn 'Arab>i says that God revealed everything from a form of science to a material form . However, Ibn Sab'>in says that God puts things in a spiritual rather than material complexion.